2019
DOI: 10.3233/jad-190604
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Tau Protein Lysine Methylation in Aging and Alzheimer’s Disease

Abstract: Tau is a microtubule-associated protein that normally interacts in monomeric form with the neuronal cytoskeleton. In Alzheimer's disease, however, it aggregates to form the structural component of neurofibrillary lesions. The transformation is controlled in part by age-and diseaseassociated post-translational modifications. Recently we reported that tau isolated from cognitively normal human brain was methylated on lysine residues, and that high-stoichiometry methylation depressed tau aggregation propensity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…We analyzed entorhinal cortex samples from donors classified as Braak stages 0-I as well as Braak stages III-IV to represent non-affected controls and early (often still clinically asymptomatic) AD, respectively (Table 1). This led to the identification of 12 phosphorylation sites which have been previously described, one novel acetylation site (Table 2) and 10 monomethylation sites, including 6 novel sites (K130, K150, K294, K298, K343, K438) and 4 described previously (K132, K259, K353, K385 (Funk et al, 2014, Huseby, Hoffman et al, 2019)). The majority of these methylated lysines is located in the repeat domains (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We analyzed entorhinal cortex samples from donors classified as Braak stages 0-I as well as Braak stages III-IV to represent non-affected controls and early (often still clinically asymptomatic) AD, respectively (Table 1). This led to the identification of 12 phosphorylation sites which have been previously described, one novel acetylation site (Table 2) and 10 monomethylation sites, including 6 novel sites (K130, K150, K294, K298, K343, K438) and 4 described previously (K132, K259, K353, K385 (Funk et al, 2014, Huseby, Hoffman et al, 2019)). The majority of these methylated lysines is located in the repeat domains (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…A recent study has suggested that Tau lysine methylation is altered in the human brain with age and differences potentially exist between control and AD patients (Huseby et al, 2019). To assess whether our sites of interest are differentially methylated between Braak 0-I and Braak III-IV patient brain samples, we used a sensitive electrochemiluminescence ELISA method using commercially available total Tau antibody-coated plates for capture and our novel methyl antibodies as detection antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations